Adjustable magnetoresistance in semiconducting carbonized phthalonitrile resin. Issue 77 (8th September 2021) - Gao, Chong; Yang, Ming; Xie, Wenhao; Zhang, Hang; Gu, Hongbo; Du, Ai; Shi, Zhong; Guo, Ying; Zhou, Heng; Guo, Zhanhu
Abstract : A controllable magnetoresistance in a carbonized phthalonitrile resin has been described. Abstract : Herein, we report the first example of controllable magnetoresistance in a semiconducting carbonized phthalonitrile resin. This special phenomenon is explained using the different ratios of graphite-like (sp 2 ) and diamond-like (sp 3 ) bonds and localization length ( a 0 ) as well as the density of states at the Fermi-level ( N ( E F )).